2022
DOI: 10.3390/cells11050773
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Aerosols Promote Oral S. aureus Colonization by Delaying an Immune Response and Bacterial Clearing

Abstract: E-cigarette (e-cig) vapor has been shown to play a pathological role in oral health and alter the oral microbiota, providing growth advantages for opportunistic pathogens. Enrichment of Staphylococcus aureus, a commensal resident in the oral cavity, correlates with the progression of periodontal disease, suggesting a role as an opportunistic pathogen. Environmental conditions, such as cigarette smoke, are known to increase S. aureus virulence, yet the role of S. aureus in periodontitis and oral preneoplasia is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Subsequently, researchers found that S. mutans adherence to OKF6/TERT-2 cells increases after aerosol treatments. Furthermore, a parallel study by Catalá-Valentín et al [87] shows OKF6/TERT-2 immunosuppression, where cytokine expression of the cells, challenged with Staphylococcus aureus, is significantly decreased after exposure to flavorless electronic cigarette aerosol. Future studies from our group aim to dissect the effects of E-liquids on the oral mucosa, specifically on (1) the cellular and molecular biology, including changes in gene expression and wound healing; (2) the physiological stress response, including glutathione and cytokine alterations; and (3) the host-bacteria interactions using both commensal and pathogenic oral species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Subsequently, researchers found that S. mutans adherence to OKF6/TERT-2 cells increases after aerosol treatments. Furthermore, a parallel study by Catalá-Valentín et al [87] shows OKF6/TERT-2 immunosuppression, where cytokine expression of the cells, challenged with Staphylococcus aureus, is significantly decreased after exposure to flavorless electronic cigarette aerosol. Future studies from our group aim to dissect the effects of E-liquids on the oral mucosa, specifically on (1) the cellular and molecular biology, including changes in gene expression and wound healing; (2) the physiological stress response, including glutathione and cytokine alterations; and (3) the host-bacteria interactions using both commensal and pathogenic oral species.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the aim of this study is to compare KSFM and DFK as media that can support OKF6/TERT-2 cell cultures, analyzing growth, morphology, tight junctions, and mucin glycoproteins gene expression, as well as tissue repair. Exploring the effects of electronic cigarette liquids (Eliquids) ± flavors, which have previously demonstrated a significant impact on the oral microenvironment [44][45][46][47][48][49][50][51], is an important research direction. From a practical point of view, toxicological experiments were also performed using E-liquids ± flavors to determine which of these two media renders the cell cultures more suitable for such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Fusobacterium nucleatum-Staphylococcus aureus interaction revealed that RadD outer membrane adhesion is partially involved in aggregate formation and that RadD-mediated interaction leads to increased expression of the global staphylococcal regulatory gene sarA [37] . Staphylococcus aureus adhesion to oral epithelial cells and bacterial biofilm formation increased with e-cigarette exposure because it led to immunosuppression, determined by reduced secretion of IL8, IL6 and IL1β by oral epithelial cells during co-culture with Staphylococcus aureus [38] . Staphylococcus aureus strains have developed several resistance mechanisms, especially in patients with chronic antibiotic treatment, in which zirconia restorations are recommended because their surface has a weaker bacterial biofilm formation compared to other biomaterials with limited microorganism adhesion characteristics which can affect the occurrence and progression of oral cavity infections [39] .…”
Section: Biofilmmentioning
confidence: 99%
“…Moreover, in vitro studies demonstrate that the flavoring agents that are combined with the aerosol of e-cigarettes have been shown to enhance DNA injury and the increase of several inflammatory proteins such as cyclooxygenase and prostaglandin E2 in gingival cells. [18,19] Chewable tobacco products such as pan, guthka, mawa, khaini, zarda, and quimam are popular. Long-term studies are required to be performed in such patients to evaluate the effects of tobacco on periodontal tissues and also to determine response to non-surgical therapy.…”
Section: Pathogens Found In Smokersmentioning
confidence: 99%